2000
DOI: 10.1002/(sici)1096-9071(200005)61:1<1::aid-jmv1>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus surface (S) transactivator with DNA-binding properties

Abstract: Chronic infection with hepatitis B virus (HBV) in humans is strongly linked to the development of hepatocellular carcinoma (HCC). Activation of growth-regulatory genes may play a crucial role in carcinogenesis. Proto-oncogene expression has been shown to be higher in HCC tissue with integrated HBV DNA than in the normal liver. Earlier, we showed that the 3' end of the HBV major surface gene (S) (426-855 nucleotides of the S region) is a transactivator of the X promoter-enhancer regulatory element in co-transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Our study showed that the preS2 domain upregulated the VEGFA promoter activity dose-dependently. As described previously, an SHBs protein with an N-terminal truncation leaving a fragment of aa 102 -226 without any preS2 domain had DNA-binding properties (22). Given all the above studies, we speculate that the HBV preS2 domain may activate the VEGFA promoter by enhancing HIF-1 stability or expression levels.…”
Section: Discussionsupporting
confidence: 71%
“…Our study showed that the preS2 domain upregulated the VEGFA promoter activity dose-dependently. As described previously, an SHBs protein with an N-terminal truncation leaving a fragment of aa 102 -226 without any preS2 domain had DNA-binding properties (22). Given all the above studies, we speculate that the HBV preS2 domain may activate the VEGFA promoter by enhancing HIF-1 stability or expression levels.…”
Section: Discussionsupporting
confidence: 71%
“…Mutations of the a‐determinant could have functional impacts on the cellular function of HBsAg as a transcriptional activator 28 . The generation of ground glass hepatocytes and subsequent development of HCC has been shown by overexpression of the large HBsAg in transgenic mice, probably mediated by the transcriptional activity of the large surface antigen (LHBsAg) 29 .…”
Section: Discussionmentioning
confidence: 99%